Identifying factor of e-Business adoption by homestay operators in Kuching Sarawak / Rebecca Dian - Dian, Rebecca (Faculty of Business and Management, 2015)
The purpose of this study is to describe the factors of e-business adoption by homes-stay operators in Kuching Sarawak. Homestay is known as a private home that tourist need to pay as they stayed as their own house and they can interact with community as well. Homestay is one of tourism product and a programme that conducted by tourism ministry that contributes in country income. Entrepreneurs in Malaysia nowadays joining this programme as it can be a second job for them to get extra income. Entrepreneur practices e-business in their business management. E-business is the administration of conducting business via internet. This would include the buying and selling of goods and services, along with providing technical or customer support through the internet (Vangei, 2015). However, not all entrepreneurs know how to take advantages from e-business. E-business still not fully utilized among homestay operators. This research involves 10 homestay operators as respondents by using semi-structured interview to get the result. All respondents need to be qualifying with participant's background. The data then analyse, and the results were recorded. The results show that some of homestay operators are not fully utilized e-business. The result also shows the factors of e business adoption by homestay entrepreneurs. There are four factors that influence entrepreneurs to apply e-business. The four factors are the gaps of age homestay operators on their communication style, the knowledge and experience of homestay operators, homestay operators about e-business awareness, and business location about their internet accessibility.